Promising properties of ALD boron nitride nanotube mats for water purification. Issue 12 (31st October 2017) - Hao, W.; Marichy, C.; Brioude, A.
Abstract : ALD BN nanotube mats are successfully applied as reusable absorptive sponges and filters for oil/organic solvents. Abstract : From a low cost template made of electrospun polyacrylonitrile fibers, a highly stable boron nitride nanotube (BNNT) mat is fabricated using low temperature atomic layer deposition (ALD) of BN. Based on polymer-derived ceramics chemistry, this ALD process permits preparation of high quality BNNTs that show superhydrophobicity, stability over a month in air and various pH conditions as well as excellent performances in water treatment. In particular, the obtained material presents high ability as a separation filter for oil from the aqueous phase in an immiscible mixture and emulsion. The BNNT mat also displays excellent reusability performances for absorption of various organic solvents and oils making this unwoven material highly promising for efficient water purification and treatment.